PENGARUH PEMANFAATAN APLIKASI GOOGLE FORM BAGI PETUGAS REKAM MEDIS UNTUK PELACAKAN ANTENATAL CARE TERHADAP WAKTU TUNGGU PELAYANAN RAWAT JALAN DI PUSKESMAS KEDUNG KANDANG KOTA MALANG - femy anggryani; Melvianus Rato Mesang (JRMIK, 2023)
Storage of medical record files of pregnant women patients is carried out in the outpatient buildingwith a centralized storage system meaning that the outpatient and inpatient medical record files arestored together in the same storage area, while the examination of pregnant women is carried out in theinpatient building or emergency room which has a distance of about 100 meters to the north of theoutpatient street. This causes officers, namely doctors or midwives, to have difficulty getting oraccessing the patient's visit history plus the patient concerned does not bring identity or KIA book whenthere are pregnant women patients with old patient status visiting suddenly to the inpatient buildingat night. this research method uses quantitative methods The purpose of this study is to make it easierfor officers, in this case doctors or midwives, to be able to access pregnant women's patient history datausing the Google Form application. With this Google Form, officers can also minimize delays in serviceto patients because the medical record data of pregnant women patients can be accessed quickly viacellphones or laptops from officers in the MCH clinic. The benefits of using Google Form are not onlyfelt by patients through effective and efficient services, but will improve the quality of service from theKedungkandang Health Center because patients feel satisfied with the services provided. Systemquality (X1) has a positive effect on waiting time (Y). Based on the SPSS output table "Coefficients"above, it is known that the Significance value (Sig) of the system quality variable is 0.553. Because thevalue of Sig. 0.553> 0.05, it can be concluded that H1 is accepted and Ho is rejected. This means that thesignificant influence between system quality (X1) on waiting time (Y). system quality, informationquality, service quality simultaneously have a significant effect on waiting time Based on the SPSS"Anova" output table above, it is known that the Significance value (Sig) is 0.625>0.05, it can beconcluded that the hypothesis is rejected or in other words, system quality (X1), information quality(X2), and service quality (X3) simultaneously have a significant effect on waiting time (Y). systemquality, information quality.